Association of type 2 diabetes mellitus and periodontal disease susceptibility with genome-wide association–identified risk variants in a Southeastern Brazilian population - Cirelli, Thamiris [UNESP]; Nepomuceno, Rafael [UNESP]; Goveia, Jéssica Marina [UNESP]; Orrico, Silvana R. P. [UNESP]; Cirelli, Joni A. [UNESP]; Theodoro, Letícia Helena [UNESP]; Barros, Silvana P.; Scarel-Caminaga, Raquel M. [UNESP] (Springer Nature, 2021)
Objective: Genome-wide association studies (GWAS) and literature have identified polymorphisms in the KCNJ11, HNF1A, IRS1, TCF7L2, CDKAL1, CDKN2B, RPSAP52, GPR45 HHEX, IL18, and RUNX2 genes associated with type 2 diabetes mellitus (T2DM) and/or periodontitis (P) in diverse populations, and we sought to evaluate them as genetic risk variants for these diseases in the Brazilian population. Material and methods: Periodontal, glycemic, and lipid data were obtained from 931 individuals divided into: control (n = 334), periodontitis (P; n = 358), and periodontitis associated with T2DM (P + T2DM; n = 239). After genotyping, associations between polymorphisms and pathologies were tested by multiple logistic and linear regressions, adjusting for age, sex, and smoking habits. Results: Considering the studied subjects, the increased risk to develop periodontitis in the periodontitis P + T2DM group was found for HNF1A-rs7957197-TA, CDKAL1-rs7754840-CG, RPSAP52-rs1531343-GC, TCF7L2-rs7903146-TT, and CDKN2B-rs7018475-GG. The association of these genetic variants for TCF7L2 and CDKN2B was confirmed for female, never smokers, and poorly controlled P + T2DM. CDKN2B-rs7018475 was associated with worse glycemic condition and periodontal parameters. Conclusion: These five reported genetic variants were associated in the studied Southeastern Brazilian population as genetic risk variants of periodontitis and T2DM associated to periodontitis as comorbidity. Gene–phenotype associations with sex and smoking habits and the CDKN2B-rs7018475 with the poor glycemic control and more severe periodontal conditions should be further investigated. Clinical relevance: Polymorphisms in the CDKAL1-rs7754840, HNF1A-rs7957197, RPSAP52-rs1531343, TCF7L2-rs7903146, and CDKN2B-rs7018475 might predispose to periodontitis and T2DM associated with periodontitis. These findings may be useful in public health genomics and future advanced clinical practice, since genetic carriage can be measured before disease onset, being of potential great benefit for treatment planning and prognosis in early disease stages.
Keywords: CDK5 regulatory subunit-associated protein 1-like 1; Cyclin-dependent kinase inhibitor 2B; Diabetes mellitus type 2; Hepatocyte nuclear factor-1 alpha; Periodontal disease; Single-nucleotide polymorphism